Ética, trabalho e formação : o serviço social em questão - Cristiano, Gabriela Dutra (2015)
This study discusses the relationship between ethics, labor and formation in Social Work from the students‟ experience from mandatory supervised internship, having as main goal to analyze the ethical derived from their everyday tasks in order to contribute to the professional formation of subjects both critically and consciously. With epistemological basis set on the historical ontological lukacsian perspective, the held research was of empirical and qualitative kind. Having as field the college courses of Social Work from PUCRS and UFRGS, and as subject‟s students on intership of level III, the data collection was developed in two stages: at first one an alternative tool in questionnaire format was applied, and in the second one semi structured interviews were held. These data were discussed through the discursive textual analysis methodology. Considering the internship as formation through work, we analyzed in this present study the the apprehension of possibilities within the needs that come from the insertion in socio-occupational spaces, the production and reproduction of values and logics historically built in the field of social politics and in the profession itself, the learning built throughout the professional formation and the everyday challenges in the work of internship students. Thus, we point that the movement made by these subjects seen in the exercise of ethics as capacity of the social being shows distances and approximation between speeches and ethical-moral acts, as well as an objectification of both conservative and emancipatory values. In this sense, we point at the need of transversal ethics in the professional formation and its centrality in the mandatory supervised internship, being this a possibility of bringing what we say closer to what we do, searching to create alternatives of possible works that have as horizon the human emancipation from all kinds of oppression and exploitation. We expect the verified results to instigate new critical reflections on a constant movement of thinking and rethinking the possibilities of a professional acting ethically and politically committed.